Revista Gestion de Las Personas y Tecnologia - Brower-Beltramin, J (UNIV SANTIAGO CHILE, FAC TECNOLOGICA, 2025)
This paper presents the most relevant results of the authors research on the new carry out the analysis, the theoretical framework used was the conceptualization of a device as knowledge/power, from the perspective of M. Foucault. In this context, the discursive expression referring to this legal language-object is described, addressing specific articles thereof. As a result of this analysis, it is verified that the developed with which the legal corpus is analytically read, delimiting and characterizing the semantic and ideological qualities contained in the law on the established, in a social context that obeys specific historical and political coordinates.